CROSS OF PARADIGMS AND COMPLEXITY IN SOCIAL ACTION RESEARCH APPROACHES - Ortecho, Mariana (2012)
This article rehearses a series of reflections on some possibilities of epistemological conciliation between qualitative and quantitative approaches to scientific inquiry. Since these initial considerations it is proposed ‘complexity’ as a perspective to overcome disciplinary approaches, related to action research processes. The final reason is to grasp the recursive process constitutive of all social phenomena, finding semantic proposals capable of integrate different levels of reading, such as quantitative structural and qualitative local survey.